Festa a Oxum: um estudo sociológico da lavagem das escadarias da catedral em Aracaju (1982-2007) - Santos, Anderson Pereira dos (2009)
The research care for Church Stepladders Wash of Our lady da Conceição accomplished by the saint's people in Aracaju (1982-2007) and its analysis under the religious perspective. We privilege describe the saint people behaviors in the festivity, the events that correspond the Party Oxum, specifically Conceição's Wash. We privilege describe the saint people behaviors in the festivity, the events that correspond the Party Oxum, specifically Conceição's Wash. Among analyzed aspects meet: The meanings attributed by the saint's people to the Stepladders Wash; The feeling and the organization of the local meaning regarding the retinue entrance in church, and the identity that Conceição's Wash takes over for saint's people. This religious manifestation has in the party your conviviality and reverence center Oxum. This way, it results of this analysis that in Aracaju the Wash party of Conceição has multiple meanings. They vary according to the paper of each subject in the party. It is seen, for example, that Conceição's Wash is a people purification rite that is present in the party Oxum. On the other hand, the investigation accomplished with the saint people of Aracaju verifies that Conceição's Wash reflects in his uncoil the difficulties of the local society. In the financial plan there are serious problems with event's organization, and in the organization plan the party lacks with terreiros limited participation of Aracaju.